UTILIZING INDONESIA’S SUPERDIVERSITY AS A LEARNING SOURCE IN CREATIVE WRITING TEACHING FOR INDONESIA EFL STUDENTS - Wenda Marlin Kakerissa; Nenden Sri Lengkanawati; Ahmad Bukhori Muslim (University of Kuningan, 2023)
Research on English creative writing has been carried out by many researchers both in Indonesia and outside Indonesia by considering how important creative writing is for learning literature in general and learning English in particular. Likewise, research on Indonesia’s super-diversity. However, research on English creative writing using Indonesian superdiversity as a learning source is still very little. Therefore, this qualitative descriptive method research is conducted. This study aims to explore benefits of teaching of creative writing utilizing Indonesia’s superdiversity as a source of learning. To achieve the aim, a questionnaire and document of students' artifacts are employed as research instruments. 59 participants from Creative Writing Language Education: Poetry class are involved; they are convenient and purposive samples. The result showed that almost all participants are very interested in learning about and making creative patterned poetry utilizing Indonesia’s super-diversity because of its many benefits. Similar research can also be carried out in other subjects so that the values of tolerance and respect become a beautiful culture amid Indonesian people's lives.